2014
DOI: 10.1017/s096719941400015x
|View full text |Cite
|
Sign up to set email alerts
|

IGF-I slightly improves nuclear maturation and cleavage rate of bovine oocytes exposed to acute heat shockin vitro

Abstract: An in vitro model of embryo production was used to examine the effects of insulin-like growth factor (IGF)-I on maturation and developmental competence of oocytes exposed to heat shock. Cumulus-oocyte complexes were matured at 38.5°C or exposed to acute heat shock (HS; 41.5°C), with or without 100 ng/ml IGF-I, for 22 h through in vitro maturation. The experimental groups were control (C), C + IGF-I, HS, and HS + IGF-I. Oocytes were fertilized at the end of maturation, and the proportion of cleaved embryos was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 51 publications
0
14
0
1
Order By: Relevance
“…In a study conducted by Zhandi et al [33], addition of 100 ng/mL IGF1 during IVM enhanced heat shock-induced apoptosis and compromised developmental competence of heatshocked oocytes. In contrast, Meiyu et al [34] found that addition of 100 ng/mL IGF1 during IVM prevented heat shock-induced apoptosis in bovine oocytes. Therefore, the objective of this study was to determine the role of IGF1 on nuclear maturation, apoptosis, mitochondrial activity, cytoskeleton organization, and developmental competence of bovine oocytes exposed to heat shock during IVM.…”
Section: Introductionmentioning
confidence: 85%
“…In a study conducted by Zhandi et al [33], addition of 100 ng/mL IGF1 during IVM enhanced heat shock-induced apoptosis and compromised developmental competence of heatshocked oocytes. In contrast, Meiyu et al [34] found that addition of 100 ng/mL IGF1 during IVM prevented heat shock-induced apoptosis in bovine oocytes. Therefore, the objective of this study was to determine the role of IGF1 on nuclear maturation, apoptosis, mitochondrial activity, cytoskeleton organization, and developmental competence of bovine oocytes exposed to heat shock during IVM.…”
Section: Introductionmentioning
confidence: 85%
“…The detrimental effect of heat shock during IVM on cleavage rate of IVF embryos is contradictory, being supported by some studies (Kalo & Roth, ; Roth & Hansen, , ), but not by others (Edwards et al, ; Edwards, Saxton, Lawrence, Payton, & Dunlap, ; Ju, Jiang, Tseng, Parks, & Yang, ). Nevertheless, it was reported that a lower percentage of oocytes developed towards 4‐cell stage at 44 hr post‐insemination when IVM was performed under heat shock conditions, suggesting that the high temperature during oocyte maturation can impair the second embryonic division (Meiyu, Liu, & Roth, ). Other study reported lower proportion of embryos with 3–4 cells at 70–72 hr post‐fertilization when in vitro maturation was performed under 40°C (Diez et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…[121] In vitro studies, wherein the addition of IGF1 to the culture medium, showed an improvement in the cleavage rate of the bovine oocytes. [122] In human developmental embryo cells, IGF-1 increases GLUT1 expression and stimulates glucose and amino acid uptake. [123] Report indicate that the expression of GLUT and the embryo translocation [124] is regulated by IGF receptors in granulosa cells human and mouse oocytes [125] , also by insulin and IGF-1.…”
Section: Transforming Growth Factor -Beta (Tgf-β)mentioning
confidence: 99%